CONTENT OF FATTY ACIDS IN CORN (ZEA MAYS L.) OIL FROM ECUADOR - W, Carrillo; C, Carpio; D, Morales; E, Vilcacundo; M, Ãlvarez; M, Silva (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The aim of this work was to determine the fatty acids content in corn seeds oil (Zea mays) sample cultivated in Ecuador. Methods: Corn oil was obtained from corn oil seeds using the cold pressing method. Methyl esters fatty acids analysis were carried out using the gas chromatography (GC) method with a mass selective detector and using the database library NIST 14.L to identify the compounds present in the corn seed oil. Results: Methyl esters fatty acids were identified from corn (Z. mays) seeds using the GC mass spectrometer (GC-MS) analytical method. Fatty acids were analyzed as methyl esters on a capillary column DB-WAX 122-7062 with a good separation of palmitic acid, stearic acid, oleic acid, elaidic acid, linoleic acid, arachidic acid, and linolenic acid. The structure of methyl esters fatty acids was determined using the GS-MS method. Corn oil has a high content of linoleic acid (omega 6) with a value of 52.68% of the total content of fatty acids in corn oil and 29.70% of oleic acid (omega 9) of the total content of fatty acids in corn oil. The sample presented a value of 12.57% of palmitic acid. Conclusions: Corn oil shows a good content of fatty acids omega 6 and 9. The higher value was of omega 6 with 52.68% content. Corn oil has a good proportion of polyunsaturated of lipids (53.80%) and 14.86% of saturated lipids.